Sourlands [videorecording (DVD)] - Flesher, Jared; Flesher, Jared; Flesher, Jared; Perez, Adrian
A provocative tale of ecology, energy, and agriculture. In the Sourlands of New Jersey, a rampaging deer herd, invasive plants, and wholesale habitat destruction threaten the local ecosystem. Farmers in the surrounding valley battle against high land prices, high property taxes, and increasingly erratic weather patterns. A group of engineers searches for new ways to save energy and stop global warming. The environmental challenges facing this community look a lot like the challenges facing ecosystems, farmers and energy visionaries everywhere.